Sustainable practices in Keylong's vernacular architecture. A detailed study of construction and thermal efficiency in the Himalayas - Singh S.D.; Shree V.; Kaur H. (My University, 2025)
This study meticulously investigates the resilience and sustainable attributes of vernacular architecture in Keylong, a paradigmatic region located in the Himalayan highlands. The research primarily concentrates on elucidating the indigenous construction techniques, materials, and their concomitant impact on thermal performance, underscoring the intersection between traditional wisdom and sustainable practices. The principal aim of this inquiry is to unravel the intricate relationship between vernacular architectural practices and their inherent sustainability, particularly in the context of the harsh climatic conditions prevalent in the Himalayan region. The objectives encompass a comprehensive analysis of the construction methodologies, material utilization, and the thermal efficiency inherent in these traditional dwellings, juxtaposed against contemporary building practices. Methodologically, the study employs a multifaceted approach, incorporating empirical data collection through state-of-the-art Tempnote TH32 dataloggers, coupled with qualitative assessments derived from local narratives and historical perspectives. This dual approach facilitates a holistic understanding of the vernacular architecture's performance and its adaptive strategies in the face of climatic adversities. The findings reveal a profound congruence between the vernacular architecture of Keylong and the principles of sustainability. The traditional constructions demonstrate remarkable thermal efficiency, primarily attributable to the judicious use of locally sourced materials and time-honored construction techniques. Moreover, these structures exhibit a remarkable resilience to the region’s extreme weather conditions, embodying a sustainable architectural paradigm that harmonizes with the natural environment. The study's outcomes underscore the significance of reviving and integrating traditional architectural wisdom into contemporary sustainable building practices. It posits that such integration could offer viable solutions to the challenges posed by climate change, especially in ecologically sensitive and high-altitude regions. This research not only contributes to the academic discourse on sustainable architecture but also provides practical insights for architects, planners, and policymakers engaged in the development of resilient and sustainable habitats in the Himalayas and similar contexts. © 2024 Singh, Shree, Kaur.